(untitled) (Heritage, 2024)
Since the proclamation of the Kingdom of Yugoslavia and the division into banovines in 1929, Niška Spa has been one of the most attractive destinations for rest and healing. This is supported by the increasing affirmation of tourism as a new economic branch, which was taken more seriously in Yugoslavia in the thirties of the 20th century. The spa’s radioactive sources made the spa one of the most famous spa-radioactive spas in the territory of Yugoslavia. Given that it is located 250 m above sea level, protected from winds and a mild climate, it could also serve as an air spa. The spa itself, according to doctors’ reports, was equipped with modern sewage and water supply, as well as electric lighting. Despite the insufficient loans from the spa administration, the spa still achieved results in terms of modern bathing facilities and accommodation for visitors. In addition to guests from all over the country and abroad, a large number of residents regularly visited the spa, mainly for bathing. However, despite the efforts made to improve the spa offer, the Banovina authorities could not overcome the private initiative, so that already in 1937, the accommodation facilities in Niška Banja passed into private ownership. Over time, the Nipka Spa attracted the urban elite of Niš and the surrounding towns, who, in competition with each other, gave the spa their stamp by building new facilities.